Prescribed sedative and other psychotropic medication use among clients attending alcohol and other drug treatment - Foulds, J.; Manning, V.; Garfield, J.; Allsop, Steve; Lam, Tina; Arunogiri, S.; Lubman, D. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Australasian Professional Society on Alcohol and other Drugs Introduction and Aims: Prescribed psychotropic medications contribute to overdose mortality among people with alcohol and other drug (AOD) disorders. We report on prescribed psychotropic medication use among AOD treatment service attendees, focusing on sedative drugs. Design and Methods: Prospective multi-site naturalistic outcome study in residential and outpatient AOD treatment facilities in Victoria and Western Australia. A convenience sample of 480 people (57% male; mean age 36.1) entering treatment were surveyed, of whom 313 (65%) were followed up by telephone interview after a median of 377 days. Participants’ prescribed psychotropic medication use was ascertained by self-report at baseline and follow-up. Results: At baseline, 41% of participants reported prescribed sedative medication (benzodiazepine, zopiclone or zolpidem) use within the past month, including prescriptions to treat withdrawal symptoms. At follow-up, the cohort reported a reduced rate of past month prescribed sedative use (23%; P < 0.001) and this rate did not significantly differ between those who continued to use their primary drug of concern and those who were abstinent at follow-up (P = 0.08). Among those with opioids as their primary drug of concern, one-third were still being prescribed a sedative at follow-up (P > 0.99 for change from baseline). At baseline, 40% of participants were prescribed an antidepressant and 13% an antipsychotic medication, which remained similar at follow-up (45% and 13%, respectively). Discussion and Conclusions: The high level of prescribed sedative drug use reported by people receiving AOD treatment is a serious public health concern given the increasing incidence of drug overdose deaths in Australia.